Proceedings of the I Iberian SLTech 2009, I Joint SIG-IL/Microsoft Workshop on Speech and Language Technologies for Iberian Languages - Dias, J.; Daniela Braga; Teixeira, A. (2009)
The ISCA Special Interest Group on Iberian Languages (SIG-IL) board, pursuing the aims of organizing conferences, schools and workshops, promoting industry/university collaboration and offering a forum to discuss opportunities in research and industry applications in the field of Speech and Language Technology, decided to organize a new event, I Iberian SLTech - I Joint SIG-IL/Microsoft Workshop on Speech and Language Technologies for Iberian Languages. A practical way of making possible the event in 2009 was to join efforts with Microsoft Language Development Center (MLDC), in Portugal, associating the SIG-IL event to a new edition of their past Workshops (I Microsoft Workshop on Speech Technology - Building bridges between industry and academia, Porto Salvo, May 2, 2007 and Propor 2008 Special Session: Applications of Portuguese Speech and Language Technologies, September 10, 2008, Curia, Portugal). The event also had the support of Red Temática en Tecnologías del Habla (RTTH). The main objective for this new event is to create a forum for the exchange of ideas and promote collaboration in the fields of Speech and Language Technologies for all the institutions who work on Iberian Languages. It also our goal to continue this event in the following years and that it may be held in the different places of the SIG-IL geography. The Organization is honoured to receive Alex Acero as keynote speaker who will bring us the following topic: “Building accurate and user-friendly speech systems”. Alex Acero is the Research Area Manager of the Speech Group in Microsoft Research, in Redmond (USA) and is one of the world leadings researchers in Speech Technology, directing an organization with 70 researchers in audio, speech, multimedia, communication, natural language, and information retrieval. He is also an affiliate Professor of Electrical Engineering at the University of Washington, Seattle. Dr. Acero is author of the books “Acoustical and Environmental Robustness in Automatic Speech Recognition” (Kluwer, 1993) and “Spoken Language Processing” (Prentice Hall, 2001). Our Scientific Committee selected the following contributions for presentation: 21 posters (3 from students), 4 recent PhDs, 2 demos and 8 groups and projects. The posters covered 6 areas: systems and applications; resources and tools; speech recognition; speech synthesis; gender, speaker and language recognition and language processing. These contributions were edited in online, CD and paper proceedings. We accepted 18 contributions with authors from Portugal, 15 from Spain, 3 from Germany, 1 from USA, 1 from Cuba and 1 from Brazil. We would like to send our special thanks to all the Chairs and Scientific Committee members that helped us in the proposals’ revision and conference organization in such a tight schedule, to our keynote speaker for bringing us such an interesting topic and to all authors for submitting the most recent advances of their work on Iberian languages speech and language processing. We expect that this is the first edition of a growing annual event that aims to attract more researchers in all countries that work on the latest advances on speech and language processing for the Iberian Languages.